2022
DOI: 10.1111/nmo.14351
|View full text |Cite
|
Sign up to set email alerts
|

Effect of colonic distension on small bowel motility measured by jejunal high‐resolution manometry

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Vis-a-vis this information, we recently performed an experimental study in healthy subjects, to determine the effect of colonic filling on small bowel motility. 28 The study showed that mild colonic filling with gas triggered a long-distance retrograde reflex: high-resolution jejunal manometry detected repeat fronts of propagated contractions, with inhibition of background of segmental contractions, a motor pattern reminiscent of the minute rhythm pattern described in this study. Conceivably, advances in the recording techniques will help to understand the significance of reactive small bowel propagated activity.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Vis-a-vis this information, we recently performed an experimental study in healthy subjects, to determine the effect of colonic filling on small bowel motility. 28 The study showed that mild colonic filling with gas triggered a long-distance retrograde reflex: high-resolution jejunal manometry detected repeat fronts of propagated contractions, with inhibition of background of segmental contractions, a motor pattern reminiscent of the minute rhythm pattern described in this study. Conceivably, advances in the recording techniques will help to understand the significance of reactive small bowel propagated activity.…”
Section: Discussionsupporting
confidence: 60%
“…We acknowledge that the value of these non‐systematic and retrospective observations is orientative at most, but it may indicate that the minute rhythm pattern may be related to a reaction to downstream pooling of contents and dumped flow; hence, it could be speculated that under these circumstances, the manometric pattern reflects a reactive pattern triggered by fecal retention. Vis‐a‐vis this information, we recently performed an experimental study in healthy subjects, to determine the effect of colonic filling on small bowel motility 28 . The study showed that mild colonic filling with gas triggered a long‐distance retrograde reflex: high‐resolution jejunal manometry detected repeat fronts of propagated contractions, with inhibition of background of segmental contractions, a motor pattern reminiscent of the minute rhythm pattern described in this study.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Small bowel motility was evaluated by a high‐resolution intestinal manometry system, as previously described 8,9 . Briefly, after an overnight fast, a customized 35‐channel water‐perfused manometry catheter designed to measure jejunal motility (Mui Scientific) was orally introduced into the jejunum under fluoroscopic guidance.…”
Section: Methodsmentioning
confidence: 99%